Leis de conservação: teoria geral - Viana, Matheus Magaiver Barbosa (2022)
In this thesis we study some aspects of the theory of Partial Differential Equations (PDE's), the theory of the existence and the uniqueness of classical solutions to the Cauchy problem u_t+f'(u)u_x=0, u(0,x)=u_0(x) in the range Π_T=[0,T)xR, where f∈C²(R) and u_0∈C¹(R). Furthermore, we will show some results on generalized solutions and build a generalized solution for functions f(u)=u³ and f(u)=sen u, both with five discontinuities lines. Next, some notions of Kruzhkov's generalized entropy solution are presented. Finally, we will discuss the solutions of the Riemann problem for a concave or convex function f and how concave or convex envelopes allow us to solve the Riemann problem for a function f∈C¹(R).